Crime and punishment Mzansi style: an exploration of the discursive production of criminality and popular justice in South Africa's Daily Sun - Boshoff, Priscilla A (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
The highly popular South African tabloid the Daily Sun, established post-apartheid in 2002, is known for its sensationalist and controversial reporting of black township life. Read by over five million black working class readers, much of its reporting concerns the crimes experienced by them and their struggles for justice. The extraordinarily high rate of violent crime in township areas for which South Africa became infamous during the 1980s did not decrease as much as hoped after the political transition in 1994 and crime overshadowed the first decades of the new administration, adding to the frustrations generated by the slow pace of social and economic reform. Part of the Daily Sun's success can be attributed to how, around these linked concerns, it fashions for its readers a particular discursive world, Sunland. It is the phatic relationship that the tabloid maintains between itself and its readers which forms the foundation upon which this textual study rests. In approaching the tabloid's representations of crime I draw on cultural criminological understandings of crime as culture and the formative relationship in this regard between crime and the media. As a preeminent site of cultural production in contemporary society, the media contribute to the ongoing definition of what constitutes crime, who is criminal and what counts as justice. This constructivist approach is congruent with Foucault's notions of discourse and the subject, and I argue that the various competing discourses about crime and justice which appear in the paper establish a set of subjectivities with which its readers may identity. The thesis explores the rhetorical and discursive means by which such subject positions are constructed within the 'grid of intelligibility' created by the Daily Sun's reportage, and using the spatial metaphor of the 'map' I trace the contours of the Daily Sun's domain with regard to crime and popular justice. To this end, the approach taken is a qualitative one which draws eclectically on a variety of interpretive methods, including semiotic, narrative and discourse analysis. Using these, I map the relations between People's Justice, the police, gender relations and witchcraft crimes, four areas chosen from a broad thematic content analysis of the complete set of editions from 2011. I show how these are not discreet but co-constructed areas within the coverage, drawing their meaning mutually from a range of conflictual relationships derived from the conditions of post-apartheid social life.
Keywords: Daily Sun (South Africa); Tabloid newpapers -- South Africa; Crime in mass media; Justice in mass media; Police in mass media; Newpapers -- South Africa; Newpapers -- Objectivity -- South Africa; Women -- Violence against -- South Africa -- Press coverage; Witchcraft -- South Africa -- Press coverage; Police -- South Africa -- Press coverage